Materials innovations in an emerging hydrogen economy : a collection of papers presented at the Materials Innovations in an Emerging Hydrogen Economy Conference February 24-27, 2008 Cocoa Beach, Florida - Materials Innovations in an Emerging Hydrogen Economy Conference (1st : 2008 : Cocoa Beach, Fla.); Wicks, George G., editor; Simon, Jack., editor; American Ceramic Society. (Hoboken, N.J. : Wiley, 2009)
FTIR